Pertimbangan Hakim dalam Menolak Dispensasi Nikah Perspektif Teori Keadilan John Rawls (Studi Penetapan Pengadilan Agama Kabupaten Kediri Nomor 0158/Pdt.P/2018/PA.Kab.Kdr) - Awal Mukmin (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2023)
This study aims to reveal how the judge's considerations in rejecting the marriage dispensation, and how the judge's decision in rejecting the marriage dispensation from the perspective of John Rawls' theory of justice. This research is an empirical legal research using a qualitative descriptive approach. Data collection techniques are interviews and documentation. Data analysis techniques are carried out by codifying data, presenting data, drawing conclusions. The analysis in this study uses John Rawls' theory of justice. The results of this study indicate that: First, the judge's consideration is the condition of the prospective bride and groom including age, economics and knowledge, readiness of both parents, the arguments for the application and statutory regulations. Second, the judge's consideration in the two determinations lies in the readiness of the prospective bride and groom in terms of age, occupation and knowledge. Third, in the perspective of John Rawls' Justice theory: First, based on the concept of original position and the veil of ignorance, the applicant as a citizen agrees that the religious court with all its regulations is an institution established to protect and provide the rights of every citizen. Second, based on the principle of freedom of basic rights, the judge's decision has two sides, on the one hand the decision has granted the applicant's rights, and on the other hand it has also prevented the applicant's rights. In the principle of difference, the difference in the results of the determination given by the judge will still provide advantages and benefits to the applicant.